Dilema Peningkatan Literasi Matematika melalui Media Pembelajaran E-colands pada Siswa Kelas VII, VIII, dan IX - Sasalia , Putri; Puspitasari, Sry Rita; Agustianingsih, Ramayanti; Demitra, Demitra; Milala, Loy Cindy Br; Oktavia, Setri (Pendidikan Matematika FKIP Universitas Mataram, 2025)
The low mathematical literacy of Indonesian students based on PISA results necessitates innovation in mathematics learning. This study aims to analyze the effectiveness of peatland-based digital comic media (Electronic comic of Peatland/E-colands) in improving junior high school students' mathematical literacy and to reveal the dilemma of improving mathematical literacy occurring in grades VII, VIII, and IX. The research method used was quantitative with a pretest-posttest group design. The research sample consisted of 23 grade VII students, 26 grade VIII students, and 26 grade IX students selected using a purposive sampling technique. Data were collected through mathematical literacy tests in descriptive form and analyzed using descriptive statistics, followed by t-test and n-gain score analysis. The results showed that E-colands media was effective in improving mathematical literacy with a medium improvement category in all classes (n-gain: VII=0.68; VIII=0.41; IX=0.55). However, a dilemma was found where the significant improvement only changed the literacy criteria from low to medium in class VII, while classes VIII and IX remained in the low category even though their scores increased. This dilemma indicates the presence of cumulative learning loss, differences in psychological and motivational factors, and the need for longer and more integrated interventions for holistic mathematical literacy improvement.